Isolation and identification of soil bacteria resistant to surfactants in washing detergents. Issue 4 (11th February 2022) - Miyoshi, Shin‐ichi; Okubo, Naomi; Mitsumori, Satoko
Abstract: Linear alkylbenzene sulfonate (LAS) and polyoxyethylene lauryl ether (POLE) are the major surfactants in washing detergents. In the present study, we isolated surfactant‐resistant bacteria from soil samples collected from a sports ground and a farm field. The samples were treated with 2.0% LAS or POLE at 25°C for 30 min and cultivated on agar plates at 25°C for several days, after which manifold bacterial colonies were isolated. Thereafter, we tested the ability of each bacterial isolate to resist the antibacterial activity of the surfactant. Ten LAS‐resistant strains were isolated, and all were found to be Gram‐negative bacteria such as Enterobacter and Pseudomonas . On the other hand, 18 POLE‐resistant strains were isolated, of which 14 were Gram‐positive bacteria including Bacillus and Microbacterium . Notably, one POLE‐resistant strain was identified as Bacillus cereus, a potential causative agent for foodborne illness. The genera of LAS‐ and POLE‐resistant bacteria did not overlap. Therefore, the combination of LAS and POLE could be more effective to eliminate soil bacteria from clothes and/or daily necessities.